Recognition of conventional expressions by EFL learners in Mexico and China. (November 2022) - Bardovi-Harlig, Kathleen; Izquierdo, Jesús; Su, Yunwen
Abstract: This paper examines the role of EFL instructional contexts in the acquisition of conventional expressions as pragmalinguistic resources. This study compares the performance of 303 EFL students in two culturally and linguistically different countries and 89 native speakers of American English. The students were enrolled in university EFL programs in China ( n = 193) and Mexico ( n = 110), and were recruited from courses that estimate the learners' proficiency to be CEFR B1. Age-matched native speakers of English were recruited from university classes on second language studies and linguistics. All groups completed an aural multiple-choice discourse completion task comprised of 20 items with options generated by native-speakers and learners during a production task. The EFL learners at the two sites, with the same level of proficiency, selected the targeted conventional expressions from the multiple-choice task with equal frequency. Most of their alternative selections showed sociopragmatic knowledge of the preferred speech act. Identical alternative choices reflect the learners' proficiency level, whereas their different choices suggest possible lexical influence from their distinct L1s. The paper ends by considering instruction and media access as variables that may account for the degree of success in the pragmatic development of conventional expressions in EFL contexts.